Remember Little Rock the time, the people, the stories - Walker, Paul Robert (Washington, D.C. : National Geographic, 2009)
Just over 50 years ago, in Little Rock, Arkansas, nine brave black students stood up for their rights and made history. The integration of Central High School in Little Rock changed the course of education in America forever, and became one of the pivotal points in the Civil Rights Movement. In Remember Little Rock award-winning author Paul Robert Walker uses eyewitness accounts and on-the-scene news photography to take a fresh look at a time of momentous consequence in U.S. history. Here, we get the story from all sides: the students directly involved; their fellow students, black and white; parents on both sides; military, police, and government officials. The author uses personal interviews with many of those who attended the 50th anniversary celebration in 2007, and explores what happened, what's changed, what hasn't, and why.
Foreword / Terrence J. Roberts, Ph. D. -- September 4, 1957 -- Jim Crow & Orval Faubus -- September 23, 1957 -- September 25, 1957 -- Student warriors -- Epilogue -- Time line -- Postscripts -- Sources -- Index.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes bibliographical references (p. 60) and index.
Description based on print version record.
Keywords: Central High School (Little Rock, Ark.) -- History -- Juvenile literature; School integration -- Arkansas -- Little Rock -- History -- 20th century -- Juvenile literature; African American students -- Arkansas -- Little Rock -- History -- 20th century -- Juvenile literature; African Americans -- Education -- Arkansas -- Little Rock -- History -- 20th century -- Juvenile literature; Central High School (Little Rock, Ark.) -- History; School integration -- Arkansas -- Little Rock -- History -- 20th century; African American students -- Arkansas -- Little Rock -- History -- 20th century; African Americans -- Education -- Arkansas -- Little Rock -- History -- 20th century; Electronic books- OSLIS; Electronic books